Landslide Hazard Mapping: GIS Based Susceptibility Assessment of Leoutikhola Watershed, Dhankuta, Nepal - Linkha, Tika Ram; Rai, Dil Kumar; Lama, Furbe (The Third Pole: Journal of Geography Education, 2019)
This article examines the landslide hazard mapping in Leoutikhola watershed of Dhankuta district, eastern hills of Nepal. The hills are regarded as one of the most vulnerable areas in the world. The area is prone to different types of natural hazards such as landslide, debris flow, gully erosion, mass wasting, and flooding. Various studies pointed out biophysical and socioeconomic factors are more responsible to landslide hazards in the hill-slope environment. This paper argues that the rainfall intensity, unscientific methods of cultivation and lack of environment friendly developmental activities in steep slope are some of the major driving factors to landslide in the Leoutikhola watershed area. Leoutikhola watershed area has been suffering from different types of natural hazards such as landslide, debris flow, gully erosion, mass wasting and flooding. Field verification and satellite imageries are the major sources for the information to analyze. Due to its fragile and very weak geological condition, geomorphic hazard is considered more common than other types of hazards which lose massive lives and property in the study area. The field observation and local people perception indicate a large amount of budget required to mitigate natural hazards in this area especially for landslide. In this context, this paper attempts to portray the landslide hazard zonation and susceptibility mapping correlated with various factors. For this purpose, bivariate statistical index and Geographic Information System (GIS) and Remote Sensing (RS) tools are used to calculate weighted values. The overall parameters indicate that in the series (-4.2 to 4.58) of five different hazard zones like very low, low, moderate, high and very high. The paper concludes that hazard determination calculated values indicate to 4.2 to -2.09, -2.09 to -1.0, -1.0 to-0.05, -0.05 to 1.24 and 1.24 to 4.58 respectively in the range of quartile series.